DOPPLER INDICES AND PERINATAL OUTCOMES IN FETUSES WITH EBSTEIN’S ANOMALY - Özge Kahramanoğlu; Oya Demirci; Lütfiye Uygur; Aydın Öcal (İstanbul Tıp Fakültesi Dergisi)
Objective: Ebstein’s anomaly (EA) is a rare congenital malformation associated with high perinatal mortality. In this study, we aimed to assess perinatal outcomes and factors associated with mortality in fetuses with EA. Material and Method: In this study, fetuses diagnosed with EA from 2016 to 2022 were included. Clinical information, ultrasonographic findings, and Doppler parameters were collected retrospectively.Result: A total of 14 fetuses with EA were included. Twelve patients had isolated EA, while one had unilateral renal agenesis and the other had mega cisterna magna. Amniocentesis was performed in six cases and normal results were obtained. Nine fetuses reached term pregnancy. All fetuses survived to birth. Three cases died in the first week after birth. Survivors were found to have lower tricuspid valve annulus diameter z score when compared with non-survivors (4.81±3.05 vs 6.97±1.26, respectively, p=0.05). Reversal pulmonary artery flow (2/11 vs 4/4 in survivors and non-survivors, respectively, p=0.01) and pulmonary atresia (1/11 vs 4/4 in survivors and non-survivors, respectively, p<0.01) were significantly more frequent in non-survivors. Conclusion: Perinatal mortality remains high in EA. Higher tricuspid valve annulus diameter z score, presence of reversal pulmonary artery flow, and pulmonary atresia during prenatal diagnosis are associated with poorer diagnosis. Future multicenter studies are warranted to identify risk factors and guide perinatal management.